2014
DOI: 10.1179/1754762814y.0000000091
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in auditory frequency discrimination and speech recognition in cochlear implant users

Abstract: The present findings suggest an association between auditory frequency discrimination and speech recognition proficiency in cochlear implant users. Although no causal link can be drawn from these data, possible reasons for this association are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 31 publications
6
15
0
1
Order By: Relevance
“…The DLF thresholds of the CI users in the current study were not associated with the F0, VTL, or F0 + VTL discrimination thresholds nor were they associated with age at implantation. Nevertheless, they were markedly reduced when compared to the NH DLF thresholds as was shown in previous studies (Goldsworthy et al 2013;Kopelovich et al 2010;Turgeon et al 2015). These findings may also favor the view that age at implantation affects high-order auditory functions rather than it affects low-level spectral resolving abilities.…”
Section: Psychophysicssupporting
confidence: 76%
“…The DLF thresholds of the CI users in the current study were not associated with the F0, VTL, or F0 + VTL discrimination thresholds nor were they associated with age at implantation. Nevertheless, they were markedly reduced when compared to the NH DLF thresholds as was shown in previous studies (Goldsworthy et al 2013;Kopelovich et al 2010;Turgeon et al 2015). These findings may also favor the view that age at implantation affects high-order auditory functions rather than it affects low-level spectral resolving abilities.…”
Section: Psychophysicssupporting
confidence: 76%
“…Numerous studies have reported that post-lingual CI users have significantly poorer frequency discrimination ability than NH listeners (Gfeller et al, 2007; Kang et al, 2009; Limb & Roy, 2014; Turgeon et al, 2015). Several factors have been reported to negatively affect the ability to discriminate frequencies in CI users.…”
Section: Discussionmentioning
confidence: 99%
“…The capability of discerning small frequency changes and fine cues in the spectral dimension plays a crucial role in speech understanding (Gifford et al, 2014; Won et al, 2014; Kenway et al, 2015). Numerous studies reported that post-lingual CI users demonstrate poor frequency discrimination (Gfeller et al, 2007; Kang et al, 2009; Limb & Roy, 2014; Turgeon et al, 2015). Moreover, the frequency discrimination performance varies substantially among patients, who typically have heterogeneous demographic variables (e.g., duration of deafness, age of implantation, and the degree of residual hearing etc.).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have used frequency discrimination or pitch ranking tasks, in which participants are required to identify the target frequency that is different from the reference frequency or to determine which of the presented sounds is higher in pitch. These studies have shown that CI users' ability to discriminate frequencies is significantly correlated with speech performance (Kenway et al, 2015;Turgeon et al, 2015). Because speech or melody perception requires the ability to detect dynamic frequency changes or relative pitch (McDermott and Oxenham, 2008), it is important to examine CI users' ability to detect frequency changes contained within a stimulus.…”
Section: Introductionmentioning
confidence: 99%